Human mTOR transcript contains an IRES element that guarantees its expression and function under global translation impairing conditions - Menezes, Juliane (2017)
Mammalian target of rapamycin (mTOR) is a conserved serine/threonine kinase that integrates signals from the cellular nutrient- and energy-status, acting namely on the protein synthesis machinery. Due to its role in regulating protein synthesis, mTOR signaling, and consequently its deregulation, is implicated in major diseases, such as cancer. Although the regulation of mTOR gene expression is not well known, major advances are emerging regarding the regulators and effects of mTOR signaling pathway. The present work demonstrates that human mTOR transcript harbors an internal ribosome entry site (IRES) element formed by a highly folded RNA scaffold capable of binding directly to the 40S ribosomal subunit. In addition, it is demonstrated that IRES-dependent translation of mTOR is stimulated by hypoxia with associated eIF2α phosphorylation, in a hypoxia-inducible factor 1α (HIF1α)-independent manner. This activation status in response to translational adverse conditions parallels mTOR protein levels. Moreover, our data reveal that the IRES-dependent translation of mTOR is necessary for its ability to induce cell cycle progression into S-phase. These results suggest a novel regulatory mechanism of mTOR gene expression that integrates the protein profile rearrangement triggered by global translational inhibitory conditions.